Purification of Kurisi (Nemipterus nematophorus) Fish Oil Derived from Surimi Processing Products - Sugeng Heri Suseno; Muhammad Anugerah Ramadhan; Nurdiansyah Albarokah (Jurnal Ilmu Pertanian Indonesia, 2026)
Kurisi fish oil is a promising omega–3 fatty acid source, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). In Indonesia, this oil is commonly obtained from a surimi processing industry product. It is predominantly utilized as an additive in animal feed due to its failure to meet the quality standards required for human consumption. Therefore, purification is essential to enhance its quality and broaden its potential applications as a food–grade oil. This study evaluated the effectiveness of two purification methods: (A) a three–step process involving degumming, neutralization, and bleaching; and (A+), which includes winterization following the A process. The study commenced with the characterization of crude kurisi fish oil, followed by applying both purification techniques. Quality parameters analyzed included free fatty acids (FFA), peroxide value (PV), acid value (AV), p–anisidine value (p–AnV), total oxidation value (totox), and fatty acid composition. The results indicated that both purification methods significantly reduced oxidative degradation indicators. Notably, the A+ method yielded the most favorable results, achieving a polyunsaturated fatty acid (PUFA) content of 33.69% and demonstrating superior oxidative stability. These findings suggest that the A+ purification method effectively enhances the quality of kurisi fish oil, supporting its potential use as a functional food ingredient. Keywords: kurisi fish oil, omega–3, oxidation, fish oil purification, winterization